Ill posedness of a neural field equation with Heaviside firing rate function (2015)
We consider the initial value problem associated to the neural field equationut(x, t) = -u(x, t) + ZRm w(x, y) [1 + g(u(x, t) -u(y, t))] f(u(y, t)) dy, (x, t) Rm x (0, 1),where f is a Heaviside function, then we show that the problem is ill posed in Cb(Rm). The proof follows from a discontinuity argument apply to the equation's flow.